CAN THE "PERSONAL RECORD" ADEQUATELY PREDICT STRENGTH ENDURANCE PERFORMANCE IN A CLEAN & JERK WORKOUT: AN ANALYSIS OF THE CROSSFIT® BENCHMARK GRACE (CIPEEX, 2023)
Our objective was to predict the strength endurance performance of Clean & Jerk (C&J) from the PR (personal Record). 17 physically active individuals classified as trained for strength exercises participated in the study. The study was conducted over 2 visits. All participants underwent a bioimpedance procedure and familiarization with the C&J movements. On the second visit, the subjects underwent the actual performance of C&J. The PR was defined based on the most recent report of the highest workload lifted. The results were expressed in work time (min). The simple linear regression analysis showed a significant association between the PR records of C&J and the time performance of the same movement (p = 0.001). The relationship demonstrated a significant association between the predicted and predictor variables (r = 0.680; R2 = 0.462), suggesting that the PR would explain 46% of the C&J performance. It is concluded that the Personal Record in C&J showed significant predictive capacity with strength endurance performance times.
Keywords: Electrostimulation; Performance; VO2Max; Crossfit